Experimental Study on Frost Durability of Sprayed Glass Fibre Epoxy Mortar (GFEM)-Reinforced Concrete Specimens - Jianhui Si; Yuanhao Li; Wenshuo Sun; Xiaoyu Niu; Junpeng Ju; Lizhe He; Junlin Xiang (Buildings)
Addressing the shortcomings of currently available concrete reinforcement techniques, a new method using sprayed Glass Fibre Epoxy Mortar (GFEM) reinforcement is proposed. To investigate the effect of this method on the frost durability of concrete, a total of 156 specimens in four groups were designed, and related freezing and thawing cycle tests were conducted. The apparent morphology, mass loss rate, ultrasonic velocity, freeze–thaw damage, and strength loss rate of each group of specimens after different freeze–thaw cycles were analysed comparatively. The test results show that the concrete specimens reinforced with GFEM have a better mass loss rate after freeze–thaw cycles and ultrasonic wave velocity than the unreinforced concrete specimens. The compressive strength of specimens in group A is 24.04 MPa, and the compressive strengths of specimens in groups B, C, and D are 35.28 MPa, 35.73 MPa, and 36.37 MPa, respectively, which is higher than that of group A by 46.76%, 48.63%, and 51.29%, respectively, and 46.76%, 48.63%, and 51.29% higher than group A, respectively. It can be seen that the concrete specimens reinforced with sprayed Glass Fibre Epoxy Mortar can effectively improve the frost durability of concrete; the reinforcing effect is obvious, and in a certain range of fibre mixing, the larger the better the frost resistance. The integration of GFEM is cost-effective and improves viscosity, and the best glass fibre mix percentage is about 0.8%. A freeze–thaw damage model for GFEM-reinforced concrete was developed using the Weibull distribution theory, and an improved strength attenuation model under freeze–thaw cycles was established. By correlating the strength attenuation model with the freeze–thaw damage model, a damage evolution equation for the reinforced specimens was formulated, allowing for the prediction of freeze–thaw damage based on the number of cycles and the relative compressive strength.